2022
DOI: 10.1590/1517-8692202228022021_0453
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction Speed of Different Types of Training on Fencing Athletes

Abstract: Introduction: Fencing is a combat sport with fierce confrontation and variations in offense and defense. To a certain extent, speed is the decisive factor in winning the game. Objective: To explore the influence of different training methods on the reaction time of fencers. Method: 20 fencers were selected and divided into three groups with different fencing levels, in addition to one control group. The experimental groups trained in three 10-minute sessions a week. The control group trained for 3 hours in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…However, certain improvements in this quality can be achieved in the process of specific sports. This is confirmed by the results of previous studies [3,5,7]. Additionally, the used tests are specific to martial arts.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, certain improvements in this quality can be achieved in the process of specific sports. This is confirmed by the results of previous studies [3,5,7]. Additionally, the used tests are specific to martial arts.…”
Section: Discussionsupporting
confidence: 86%
“…Speed is one of the decisive factors for victory in martial arts. In the study by Yao [5], the influence of various training methods on the reaction rate of fencers was studied. The results confirmed the improvement of this indicator under the influence of the methods used.…”
mentioning
confidence: 99%
“…The results of this study can be compared with other research, showing that the attack speed results of Jakarta Fencing Club student-athletes showed that the average attack speed test results obtained were 7.41 m/s [16]. Meanwhile, the average effect of the attack speed test using static movement for Fencing athletes assisted by the Indonesian National Sports Committee, Aceh Province, 2023, was 4.37 m/s.…”
Section: Discussionmentioning
confidence: 58%
“…The authors argue that the adaptation of the body to speed training contributes to an increase in cardiac output at rest compared to endurance training. Yao [23] studied the effect of various training methods on the reaction time of fencers. It has been found that regardless of a student's swordsmanship level, different training methods can significantly improve his reaction time.…”
Section: Discussionmentioning
confidence: 99%